2015
DOI: 10.1371/journal.pone.0134224
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dietary Patterns and Semen Quality in a General Asian Population of 7282 Males

Abstract: ObjectiveTo explore the associations between different dietary patterns and semen quality in a general Asian male population.MethodsCross-sectional study. Healthy Taiwanese men aged 18 years or older who participated in a standard medical screening program from 2008-2013 run by a private firm were included in this study. Semen parameters including sperm concentration (SC), total sperm motility (TSM), progressive motility (PRM) and normal sperm morphology (NSM) were recorded. A dietary questionnaire was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 35 publications
(43 reference statements)
4
100
0
3
Order By: Relevance
“…The antioxidants in male reproductive health may be positively associated with semen parameters [31][32][33], fertilization rate [34], decreasing oxidative damage to spermatozoa [35,36], DNA maintenance, transfer RNA, protein synthesis [37], and the reduction of the negative effects of inflammation [36,38]. Moreover, the DASH diet recommends a reduction in sweets, meat, eggs, and fat consumption that, due to the content of sugars, saturated/trans fatty acids, and sodium, may adversely affect sperm count [28], concentration [39,40], sperm motility [29,40,41], and morphology [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidants in male reproductive health may be positively associated with semen parameters [31][32][33], fertilization rate [34], decreasing oxidative damage to spermatozoa [35,36], DNA maintenance, transfer RNA, protein synthesis [37], and the reduction of the negative effects of inflammation [36,38]. Moreover, the DASH diet recommends a reduction in sweets, meat, eggs, and fat consumption that, due to the content of sugars, saturated/trans fatty acids, and sodium, may adversely affect sperm count [28], concentration [39,40], sperm motility [29,40,41], and morphology [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The present study showed a significant negative correlation between the percent carbohydrate content of the daily food ration and both semen volume and consistency. Liu et al 10 showed that a diet referred to as the high-carbohydrate diet (assessed by using questionnaire included the frequency and amount of consumption for each food group) negatively impacted semen quality of the subjects (abnormal total sperm count and progressive motility). The same study demonstrated that males who consumed large amounts of highly sweet snacks and sugar-sweetened drinks had lower sperm counts (10 6 /mL).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that a "western pattern" diet, which is organ meats, red and processed meats, sugar, soft drinks and confectionary, pasta, rice and refined grains, potatoes, fried and fast foods, high-fat dairy products, hydrogenated fats, mayonnaise and fatty sauces, and snacks, might have a negative effect on male fertility, other recent studies have also indicated that a "prudent pattern" diet, in which more leafy green vegetables, yellow vegetables, other vegetables, tomatoes, fish and other seafood, fruits and natural fruit juices, legumes, whole grains, poultry, tea and coffee, low-fat dairy products, and vegetable oils are consumed, may benefit sperm quality. [10][11][12] Based on the available literature in PubMed, no study has been performed to assess the impact of the quantities of selected dietary nutrients on semen quality.…”
Section: E25mentioning
confidence: 99%
“…The second pattern was an unhealthy/Western dietary pattern which was characterized by high consumption of red and/or processed meat, refined grain, sweets, high‐fat dairy products, butter, potato, high‐fat gravy, and low intake of fruit and vegetables (Gaskins et al ., ; Cutillas‐Tolin et al ., ; Liu et al ., ; Jurewicz et al ., ,b).…”
Section: Methodsmentioning
confidence: 99%